Análise da evolução do Sars-Cov-2 no Rio Grande do Sul e reflexões acerca do modelo de distanciamento controlado - Maicon dos Santos Rodrigues.; Érica Insaurriaga Megiato; Ricardo de Sampaio Dagnino; Lucas Manassi Panitz.; Eliseu José Weber (Confins)
The Covid-19 pandemic reached Rio Grande do Sul (RS), highlighting the need for a multidisciplinary and systematic approach, seeking emerging responses. The lack of a national strategy to combat the new coronavirus required the elaboration of an alternative by the local government. The option adopted was a controlled distance model, considering the health system management, aiming at guaranteeing the capacity to attend the sick due to Covid-19 and other diseases, and allowing the functioning of the economic sectors. This article provides an overview of the confirmation of cases of Covid-19 in Rio Grande do Sul, analyzes the evolution of the disease from February to October 2020, and gives a critical commentary on the controlled distance model applied by the state government. Reflections are made on the objectives of such a model, which express an attempt to condition the population’s spatial practices, and on the efficiency of the instrumentalization of social control symbolized by colors indicating the intensity of restrictions.